2020
DOI: 10.3389/fimmu.2020.02185
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Development and Function of Regulatory T Cells – Lessons for a Better Understanding of MicroRNA Biology

Abstract: MicroRNAs (miRNAs) have emerged as critical posttranscriptional regulators of the immune system, including function and development of regulatory T (Treg) cells. Although this critical role has been firmly demonstrated through genetic models, key mechanisms of miRNA function in vivo remain elusive. Here, we review the role of miRNAs in Treg cell development and function. In particular, we focus on the question what the study of miRNAs in this context reveals about miRNA biology in general, including context-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Tregs accumulate in TME and are attracted by chemokines (CCL17, CCL22, and CCL1) and exert negative regulation on T lymphocytes and on dendritic cells through the secretion of immunosuppressive cytokines and growth factors such as IL-10 and TGF-β and the expression of co-inhibitory receptors (PD-1 and CTLA4) [ 78 ]. Among all investigated miRNAs, miR-155, miR-181, and miR-17-92 play key roles in Treg differentiation and function [ 79 ]. Recently, the lncRNA Flatr has been identified as a key regulator in Tregs switch, promoting Foxp-3 expression in vitro [ 80 ].…”
Section: Ncrna In Immune Escapementioning
confidence: 99%
“…Tregs accumulate in TME and are attracted by chemokines (CCL17, CCL22, and CCL1) and exert negative regulation on T lymphocytes and on dendritic cells through the secretion of immunosuppressive cytokines and growth factors such as IL-10 and TGF-β and the expression of co-inhibitory receptors (PD-1 and CTLA4) [ 78 ]. Among all investigated miRNAs, miR-155, miR-181, and miR-17-92 play key roles in Treg differentiation and function [ 79 ]. Recently, the lncRNA Flatr has been identified as a key regulator in Tregs switch, promoting Foxp-3 expression in vitro [ 80 ].…”
Section: Ncrna In Immune Escapementioning
confidence: 99%
“…A number of apoptosis-regulating ncRNAs have essential roles in this regard. For instance, miR-155 and miR-17~ 92 are involved in differentiation regulatory T cells (Tregs) and their function ( 99 ). miR-21 and miR-26 through down-regulation of TAP1 and reduction in expression of HLA class I antigens affect response to immunotherapies ( 100 ).…”
Section: Ncrnas Cell Apoptosis and Immunotherapymentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small, single-stranded, noncoding RNAs of 18–24 nucleotides that play key roles in many biological processes, including cell proliferation, differentiation, stress resistance and apoptosis by regulating gene expression at the post-transcriptional level [ 1 , 2 , 3 ]. Numerous studies have found that changes in miRNA expression are closely related to the occurrence of various diseases, such as cardiovascular disease, obesity, diabetes and tumors [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%